2011
DOI: 10.3390/su3030500
|View full text |Cite
|
Sign up to set email alerts
|

The Soil Microbial Community and Grain Micronutrient Concentration of Historical and Modern Hard Red Spring Wheat Cultivars Grown Organically and Conventionally in the Black Soil Zone of the Canadian Prairies

Abstract: Micronutrient deficiencies in the diet of many people are common and wheat is a staple food crop, providing a carbohydrate and micronutrient source to a large percentage of the world's population. We conducted a field study to compare five Canadian red spring wheat cultivars (released over the last century) grown under organic and conventional management systems for yield, grain micronutrient concentration, and soil phospholipid fatty acid (PLFA) profile. The organic system had higher grain Zn, Fe, Mg and K le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…It was bred in 1999 (not specifically for organic production), and usually has greater yield, more resistance to stem-base and leaf diseases, better grain quality and more weed suppression than other wheat cultivars (Anonymous 1999;Ku s et al 2010). Other cultivars may have had different effects on soil microbial communities (Nelson et al 2011). There was often inconsistency between microbial community structure and disease severity and grain yield. Pathogen:antagonist ratios were not always correlated with disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…It was bred in 1999 (not specifically for organic production), and usually has greater yield, more resistance to stem-base and leaf diseases, better grain quality and more weed suppression than other wheat cultivars (Anonymous 1999;Ku s et al 2010). Other cultivars may have had different effects on soil microbial communities (Nelson et al 2011). There was often inconsistency between microbial community structure and disease severity and grain yield. Pathogen:antagonist ratios were not always correlated with disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variation and genomic regions associated with the uptake of micronutrients have also been reported in wheat [40,41]. Nelson et al [42] found, however, that the percent of arbuscular mycorrhizal fungi was negatively correlated with iron and zinc concentrations in winter wheat, but positively correlated with manganese, copper, and potassium. Mycorrhizal fungi play an important role in soil fertility and nutrient uptake in OF systems, whereas in CF their presence is severely reduced [43].…”
Section: Traits and Sources Of Variationmentioning
confidence: 94%
“…Genetic variation in grain Se concentration has been reported for a number of cereals (Table 1). Although several studies have suggested little genetic variation in grain Se concentration among bread wheat (Triticum aestivum L.) genotypes (Table 2; Lyons et al, 2005a;Zhao et al, 2009;Lee et al, 2011;Nelson et al, 2011), other studies have reported significant genetic variation in this trait (Garvin et al, 2006;Murphy et al, 2008;Rodrı ´guez et al, 2011;Pu et al, 2014). It is evident that the expression of this trait in bread wheat is strongly dependent upon weather conditions, crop husbandry and Se fertilization (Lyons et al, 2005a;Garvin et al, 2006;Zhao et al, 2009;Lee et al, 2011;Nelson et al, 2011).…”
Section: Variation In Selenium Accumulation Within Plant Speciesmentioning
confidence: 99%